Potential of siRNA in COVID-19 therapy: Emphasis on in silico design and nanoparticles based delivery - Fopase, Rushikesh; Panda, Chinmaya; Rajendran, Amarnath P.; Uludag, Hasan; Pandey, Lalit M. (Frontiers in Bioengineering and Biotechnology, 2023)
Small interfering RNA (siRNA)-mediated mRNA degradation approach have imparted its eminence against several difficult-to-treat genetic disorders and other allied diseases. Viral outbreaks and resulting pandemics have repeatedly threatened public health and questioned human preparedness at the forefront of drug design and biomedical readiness. During the recent pandemic caused by the SARS-CoV-2, mRNA-based vaccination strategies have paved the way for a new era of RNA therapeutics. RNA Interference (RNAi) based approach using short interfering RNA (siRNA) may complement clinical management of the COVID-19. RNAi approach will primarily work by restricting the synthesis of the proteins required for viral replication, thereby hampering viral cellular entry and trafficking by targeting host as well as protein factors. Despite promising benefits, the stability of siRNA in the physiological environment is of grave concern as well as site-directed targeted delivery and evasion of the immune system require immediate attention. In this regard, nanotechnology offers viable solutions for these challenges. The review highlights the potential of siRNAs targeted toward specific regions of the viral genome and the features of nanoformulations necessary for the entrapment and delivery of siRNAs. In silico design of siRNA for different variants of SARS-CoV-2 has been discussed. Various nanoparticles as promising carriers of siRNAs along with their salient properties, including surface functionalization, are summarized. This review will help tackle the real-world challenges encountered by the in vivo delivery of siRNAs, ensuring a safe, stable, and readily available drug candidate for efficient management of SARS-CoV-2 in the future.